Perancangan Sistem Informasi Akuntansi Penggajian Pegawai Instansi Pemerintah di BKPSDM Kab. Cianjur - Ayuni, Putri; Perwito, Perwito; Abdussalam, Falaah (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2024)
The process of employee payroll system at BKPSDM Kab. Cianjur Agency already uses a computer but it is not optimal because it still uses Microsoft Excel in data collection and calculation salaries. The purpose of this research is to create a computerized payroll information system that make it easier for agency in the payroll process for employees and minimize the problems that often occur. This information system designed using PHP Myadmin programming language and MySQL as a database. The approach to developing this system uses the waterfall method and the tools involved include Flowmap, Context Diagram, Data Flow Diagrams (DFD), and Entity Relationship Diagrams (ERD). The results of this employee payroll application can make it easier to collect employee data and calculation of employee salaries accurately and can streamline time in making reports so as to reduce errors in the employee payroll system. Keywords: accounting information system; payroll; waterfall